Structural and biochemical investigations on DNA accessibility and dynamics within the nucleosome - Edayathumangalam, Rajeswari S., author; Luger, Karolin, advisor; Anderson, Oren P., committee member; Nyborg, Jennifer K., committee member; Peersen, Olve B., committee member; Stargell, Laurie A., committee member (Colorado State University. Libraries, 2005)
The 'blueprint of life' is organized as highly compacted chromatin in the eukaryotic nucleus. The fundamental building block of chromatin is the nucleosome, which comprises the nucleosome core particle in association with 20 to 80 bp of linker DNA and the linker histone protein. The nucleosome core particle, which is the first step of compaction of naked DNA, consists of 147 bp of DNA wrapped around an approximately equal mass of a proteinaceous histone octamer. The nearly 100,000-fold level of final compaction of DNA achieved in the nucleus places heavy restraints on the cellular machinery. Processes like transcription, DNA replication, DNA repair and recombination, which use DNA as the working platform, must now navigate this very tightly packed scaffold to gain access to specific target sites. Understanding how the cell maintains the fluidity and dynamics of the underlying DNA without compromising the structural integrity of chromatin will provide invaluable insights into the mechanistic details of biological processes like transcription. We approach these questions using the monunucleosome as a model system and pyrrole-imidazole polyamides as small-molecule probes for DNA accessibility and dynamics. First, we perform in vitro temperature-induced nucleosome repositioning assays and show that polyamides inhibit the temperature-induced translocation of the histone octamer on the DNA, thereby suggesting a mechanism for temperature-induced nucleosome repositioning. Second, we report the co-crystal structure of the nucleosome core particle in complex with a 'bivalent' polyamide dimer 'clamp'. The clamp targets a nucleosomal 'supergroove' (two non-contiguous sites that are 80 bp apart on linear DNA) and significantly improves nucleosome crystal diffraction as well as dramatically stabilizes nucleosomes against dilution-induced dissociation in vitro. These findings identify 'supergrooves' as unique platforms for molecular recognition of condensed DNA. Third, using x-ray crystallography and footprinting techniques, we demonstrate that nucleosomal DNA exists as a mixture of multiple twist-defect intermediates in solution. Fourth, the structure of a tailless H 4-containing nucleosome bound by a polyamide shows that ligand binding leads to unraveling of the ends of the nucleosomal DNA. This also leads to an alternate mode of crystal packing, which does not involve the DNA ends, and thereby reveals other possible interactions between nucleosomes. Taken together, these studies elucidate how the various components resident within the nucleosome modulate nucleosome stability, accessibility, and dynamics. Our results also further our understanding of compacted DNA as a biological substrate.
Keywords: molecular biology; biophysics